Use of functional genes to quantify denitrifiers in the environment. (20th January 2006) - Philippot, L.
Abstract : During the last decade, application of molecular methods using cultivation-independent approaches has provided new insights into the composition and structure of denitrifying communities in various environments. However, little is known about their abundance, and quantification is still performed using cultivation-based approaches, which are not only biased by the inability to cultivate of many micro-organisms but also fastidious and time-consuming. Two types of cultivation-independent approaches have recently been developed to quantify denitrifiers. The first type, which is based on the hybridization technique, comprises the use of Southern hybridization and DNA arrays. The second type, based on PCR, comprises the use of MPN (most probable number)-PCR, competitive PCR or real-time PCR. In this review, these different approaches will be presented with examples of their application in environmental studies.